Smart Cities Atlas Western and Eastern Intelligent Communities - Riva Sanseverino, Eleonora; Riva Sanseverino, Raffaella; Vaccaro, Valentina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book discusses the concept of the smart city, and is based on a multi-service and multi-sectoral approach to urban planning, including various urban functions and the human capital of cities. The work is divided into three parts. The first is an introductory section which covers definitions, policies and tools used at European level for the development and classification of a smart city. The second presents a selection of examples of Western and Eastern communities, which experienced technologies and strategies that have made them smart. The third describes in detail the main three possible approaches (economical, technological and social) to the smart city concept which are the focus ambits of the holistic concept of smart city. The work provides a good overview of the concept of smart city, and also offers a critical analysis of the various approaches to smart cities, in order to provide tools to develop solutions that address the smart development of cities with an approach as multi-sectoral as possible. Its accessible language and several examples make the book easy to read and appealing to public administrators, students, planners and researchers.
Part I: Smart city: definitions, policies, tools -- Chapter 1: General overview -- Chapter 2: Experiencing the smart city concept: the challenge of intelligent districts -- Part II: Smart City Atlas -- Chapter 3: Smart cities: case studies -- Part III: Approaches to the smart city concept: economy, technology, people -- Chapter 4: For a "living (lab)" approach to smart cities -- Chapter 5: Civic Crowd Funding: sharing economy financial opportunity to smart cities -- Chapter 6: Smart Community Infrastructures -- Chapter 7: The role of sharing practices and dematerialized services in smart cities -- Chapter 8: The role of technology in participative processes -- Chapter 9: Sustainable regeneration of brownfields -- Chapter 10: Shared administration for smart cities -- Chapter 11: A holistic vision of Smart cities: an opportunity for a big change -- Chapter 12: A theological perspective towards smart communities.
Keywords: Sociology, Urban; Energy policy; Energy and state; Operations research; Civil engineering; Urban Sociology; Energy Policy, Economics and Management; Operations Research and Decision Theory; Civil Engineering